Assessment of TD-DFT- and TD-HF-based approaches for the prediction of exciton coupling parameters, potential energy curves, and electronic characters of electronically excited aggregates - Liu, Wenlan; Dreuw, Andreas (Journal of computational chemistry, 2011)
The reliability of linear response approaches such as time-dependent Hartree-Fock (TD-HF) and time-dependent density functional theory (TD-DFT) for the prediction of the excited state properties of 3,4;9,10-tetracarboxylic-perylene-bisimide (PBI) aggregates is investigated. A dimer model of PBI is investigated as a function of a torsional motion of the monomers, which was shown before to be an important intermolecular coordinate in these aggregates.
Gesehen am 18.12.2017